1998
DOI: 10.1007/s004649900644
|View full text |Cite
|
Sign up to set email alerts
|

In vivo study of meshes implanted over the inguinal ring and external iliac vessels in uncastrated pigs

Abstract: Abnormal healing processes after implantation of polypropylene mesh may increase complications of the transabdominal preperitoneal and total extraperitoneal approaches in laparoscopic inguinal hernia repair, whereas the minimal response to ePTFE meshes may make them safer for use in the preperitoneal space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 10 publications
1
23
0
1
Order By: Relevance
“…11,15 The testicular veins may also be affected by the inflammatory reaction due to the prosthetic mesh. Le Blanc et al 8 and Peiper et al 6 have noted testicular venous congestion after mesh implantation in animal studies. Additionally, Peiper et al 6 described thrombosis within the spermatic cord.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…11,15 The testicular veins may also be affected by the inflammatory reaction due to the prosthetic mesh. Le Blanc et al 8 and Peiper et al 6 have noted testicular venous congestion after mesh implantation in animal studies. Additionally, Peiper et al 6 described thrombosis within the spermatic cord.…”
Section: Discussionmentioning
confidence: 97%
“…7 The same study showed that the response, which was at its maximum at 3 weeks, gradually decreased over the next 6 months. Also, LeBlanc et al 8 placed a heavy polypropylene mesh into the preperitoneal space and observed severe adhesions to the spermatic cord 30 days after implantation. Fitzgibbons et al 9 found adhesions between the mesh and the spermatic cord even after intraperitoneal placement of the mesh, probably due to the inflammatory reaction.…”
Section: Discussionmentioning
confidence: 97%
“…Different mesh material induces various grades of foreign body reaction and chronic inflammation [13]. Perivascular cuffing, calcifications, ossifications and necrosis of soft tissue have been observed in animal experiments especially with polypropylene meshes [13]. Furthermore, a significant shrinking of the wound as well as the mesh is noted [14].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic hernia repair is similar to open repair and depends on the use of synthetic meshes [11,12]. Different mesh material induces various grades of foreign body reaction and chronic inflammation [13]. Perivascular cuffing, calcifications, ossifications and necrosis of soft tissue have been observed in animal experiments especially with polypropylene meshes [13].…”
Section: Discussionmentioning
confidence: 99%
“…El uso indiscriminado de mallas aloplásticas en las hernias inguinales tiene dos inconvenientes: La acción a largo plazo de las mallas sobre los tejidos, la posibilidad de migración y de daño sobre estructuras vecinas 35,36 . Sin dejar de lado la importancia del conocimiento de la anatomía y fisiología de la pared abdominal por el cirujano, así como su experiencia y excelencia en el manejo de las estructuras anató-micas del abdomen, el uso de las mallas pone a su disposición la posibilidad de restablecer la continuidad de la pared abdominal o de reforzar los tejidos debilitados.…”
Section: Utilización De Las Mallas Sintéticas No Absorbibles En El Trunclassified